Data Hiding Scheme on Medical Image using Graph Coloring. (May 2015) - Astuti, Widi; Adiwijaya; Wisety, Untari Novia
Abstract: The utilization of digital medical images is now widely spread[4]. The medical images is supposed to get protection since it has probability to pass through unsecure network. Several watermarking techniques have been developed so that the digital medical images can be guaranteed in terms of its originality. In watermarking, the medical images becomes a protected object. Nevertheless, the medical images can actually be a medium of hiding secret data such as patient medical record. The data hiding is done by inserting data into image - usually called steganography in images. Because the medical images can influence the diagnose change, steganography will only be applied to non-interest region. Vector Quantization (VQ) is one of lossydata compression technique which is sufficiently prominent and frequently used. Generally, the VQ based steganography scheme still has limitation in terms of the data capacity which can be inserted. This research is aimed to make a Vector Quantization-based steganography scheme and graph coloring. The test result shows that the scheme can insert 28768 byte data which equals to 10077 characters for images area of 3696 pixels.